PEMAHAMAN MASYARAKAT TENTANG PERBANKAN SYARIAH (Studi Kasus Kampung Rancabango) - DEPI PURNAMASARI (CV. Kalimasada Group, 2025)
Islamic banking is a financial system that operates based on Islamic sharia principles, such as the prohibition of usury, speculation, and unfair transactions. Although it has developed rapidly in Indonesia, the level of public understanding of the concept and mechanisms of Islamic banking still varies. This study aims to determine the public's understanding of Islamic banking (Case Study of Rancabango Village). This study uses a qualitative descriptive approach, with observation and literature review. Qualitative methods are research procedures that produce descriptive data in the form of written or spoken words from people and observed behavior. Descriptive methods describe the nature of something that occurs at the time of the research and examine the causes of a phenomenon. The results of the study indicate that the level of public understanding of Islamic banking is low to moderate. Although some people are aware that Islamic banking does not use interest and operates based on Islamic sharia principles, their understanding of the concept of contracts, profit-sharing systems, and Islamic products as a whole remains limited. Several factors influencing this level of understanding include education level, religious background, experience using Islamic banking services, and access to information and education about the Islamic banking system. Therefore, more intensive outreach, education, and Islamic financial literacy efforts are needed by the government, Islamic financial institutions, and educational institutions to better understand and utilize Islamic banking services optimally and in accordance with Islamic principles.